Study of visual field changes in patients with multiple sclerosis - رجب محمود; سعيد هالة; امين شيراز (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: Our aim is to investigate visual field defects in patients with multiple sclerosis and to determine the most common type of defect in the case of a history of optic neuritis or the absence of it. Methods: The visual field examination was conducted with Octopus900 device in patients with multiple sclerosis ـTwenty-one patients (41 eyes), a detailed medical history was taken, age and gender informations was recorded, and a comprehensive ophthalmological examination was performed, including examination using a slit lamp for the anterior sections of the eye and the poseterior sections of the eye, and the intraocular pressure of all patients was measured using Goldman device. We divided patients with multiple sclerosis into two groups according to the clinical history: With a previous history of optic neuritis MS-ON No history of optic neuritis MS- NON The visual field was examined by Octopus900. Results: In this study, we found that 11 eyes )84.6%( of patients with multiple sclerosis with a history of an attack of optic neuritis suffered from central scotoma, and central scotoma were found in 13 eyes )46.4%( of patients without a history of an attack of optic neuritis and Another -type of scotoma in 6 eyes with a rate of 21.4% Conclusion: Multiple sclerosis causes defects in the visual field, whether with or without optic neuritis, and these defects are often central scotoma.